Strategi Pembelajaran Berbasis Kecerdasan Emosional bagi Peserta Didik Generasi Z di Madrasah Ibtidaiyah - Danar Nanda Rachmawati; Gaguk Setiawan (Kartika: Jurnal Studi Keislaman, 2026)
The development of digital technology has transformed the learning characteristics and needs of Generation Z while presenting challenges in emotional regulation, motivation, and social interaction. This study aims to analyze learning strategies based on emotional intelligence that are relevant to Generation Z in the context of primary education. The study employed a qualitative approach using a library research method. Data were obtained from relevant scientific literature on Generation Z, emotional intelligence, and learning strategies and analyzed descriptively through selection, categorization, and thematic synthesis. The results show that four strategies gamification, visual and multimedia learning, Project-Based Learning, and edutainment are relevant to developing five dimensions of emotional intelligence: self-awareness, self-regulation, self-motivation, empathy, and social skills. Gamification is particularly associated with emotional regulation and self-motivation through feedback, while Project-Based Learning and collaborative learning support the development of empathy and social skills. Visual media and edutainment can foster self-awareness through reflection on social situations. The study also identifies implementation risks, including excessive orientation toward scores, limited deep-text literacy, free-rider behavior, and the dominance of entertainment over learning substance. These findings indicate that learning strategies for Generation Z should integrate technology with reflective activities, collaboration, and assessment while maintaining substantive learning and higher-order thinking development